DEVELOPMENT OF WEB PROGRAMMING LEARNING MEDIA USING LARAVEL BASED ON PROJECT BASED LEARNING MODEL IN THE DEPARTMENT OF INFORMATICS AND COMPUTER ENGINEERING FT UNM - Mustari Lamada; Syahrul Syahrul; Nurul Izzah Qurratu'aini (Lembaga Penelitian Mahasiswa Penalaran UNM, 2023)
This research aims to determine the results of developing web programming learning media using Laravel based on the project-based learning model in the Department of Informatics Engineering and Computer Science at UNM that meet the criteria of validity, practicality, and effectiveness. This research used the research and development (R&D) method by applying the ADDIE development model. Data were collected through interviews, questionnaires, tests, and documentation. Two groups of subjects involved in this study were validators, consisting of two expert lecturers, and students of the Department of Informatics Engineering and Computer Science at UNM who took the Web Programming course in 2021, totaling 34 people. Data analysis was performed using descriptive quantitative analysis methods as well as pretest and posttest analysis using prerequisite tests and non-parametric Wilcoxon tests with the assistance of SPSS software version 25. The results of the study show that web programming learning media using Laravel based on the project-based learning model has met the criteria as valid, practical, and effective learning resources. The developed learning media received positive validation from media/system experts with a feasibility rate of 100%. Students' response to this learning media was also positive, with a practicality rate of 84.5%. In addition, the use of this learning media significantly improved students' learning outcomes, as evidenced by an average increase in post-test scores of 67.80%.